Radio echo sounding in the area of the Yamato Mountains - Wada, Makoto; Yamanouchi, Takashi; Mae, Shinji; Kusunoki, Kou (1981)
P(論文) In the bare ice area of the Yamato Mountains about 4000 pieces of meteorite were found by the Japanese Antarctic Research Expedition (JARE). The most plausible explanation of the mechanism of meteorite concentration in the area was presented by NAGATA. In order to survey the bedrock topography in the bare ice area airborne radio echo sounding was carried out in January 1980. The new sounder (NIPR-A) was operated at 179 MHz and mounted in a Pilatus Poter PC-6. The peak power of the sounder was approximately 1kW and the pulse width was 0.3μs. The line of the survey consisted of 5 parts, each being 80km long. Two of them were parallel to the north-south direction and three were parallel to the east-west direction. Their interval was about 30km. In this paper, the result of the survey on the topography of the bedrock and the surface is reported and especially the ice flow near Motoi Nunatak where the flow velocity and the ablation rate of ice were measured is commented. The bare ice area where a lot of meteorites were found is a flat surface area upstream of subsurface mountains. departmental bulletin paper